Corridor developments for transforming Central Asia - Satoru Kumagai; Toshitaka Gokan; Kenmei Tsubota (Asian Development Bank Institute (ADBI), 2021)
This paper offers a Spatial Computable General Equilibrium Model (SCGE) to evaluate the potential regional economic impacts of the Central Asia Regional Economic Cooperation Program (CAREC) corridors and the Trans-Caspian International Transport Route (TITR). We base our model on spatial economics and incorporate sub-national data over the regions. We also equip the model with multimodal choices among trucks, trains, airplanes, and ships, which are crucial for the analysis of landlocked regions like Central Asia. Through scenario-based simulations, we find that economic impacts are not spatially limited to the regions with the projects. It is probable that population and industries may shift to regions with better connectivity by virtue of corridor developments. There would also be synergy effects from the implementation of both the CAREC and the TITR corridor, meaning that the two projects have a complementary relationship. Furthermore, the analysis reveals that the economic impacts of the projects may derive largely from the growth in the service sector, suggesting the need for additional public investments, such as Special Economic Zones, to boost industries other than services.
Keywords: C68; O18; R30; 330; impacts of infrastructures; economic development; spatial computable general equilibrium